Hydrogeologic configuration of the Dunas/Barreiras aquifer system in the north zone of Natal City, Rio Grande do Norte, Brazil - Vasconcelos, Mickaelon Belchior; de Melo, José Geraldo; Demétrio, José Geilson Alves (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
The residential occupation of the north zone of Natal city began in the 1970’s, changing the characteristics of the agricultural area to an urbanized area. Groundwater represents approximately 44% of the local freshwater reserves, supplied by the aquifer system Dunas/Barreiras. Due to the importance of the groundwater, this study was developed in order to get the configuration of the hydrogeological structure of the Dunas/Barreiras aquifer by the identification of its saturated thickness, the flow directions and geologic conditioning through the following activities: i) the acquisition of depth profiles on wells drilled in the study area; ii) analysis of previous works with information from the hydrodynamic parameters; iii) field steps to verify the geological conditioning; iv) collecting of static level data; v) drilling of a research well. The data integration have identified the possible tectonic processes operating in the study area, as well the configuration of the geological structure. The groundwater flow was found to be homogeneous between the years 1997 and 2008, presenting an outline similar loads potentiometric and hence the same flow patterns.
Keywords: Dunas/Barreiras aquifer system; Urban groundwater; Configuration hydrogeologic